Arable weed seeds as indicators of regional cereal provenance: a case study from Iron Age and Roman central-southern Britain - Lodwick, L (Springer Berlin Heidelberg, 2018)
The ability to provenance crop remains from archaeological sites remains an outstanding research question in archaeology. Archaeobotanists have previously identified the movement of cereals on the basis of regional variations in the presence of cereal grain, chaff and weed seeds (the consumer–producer debate), and weed seeds indicative of certain soil types, principally at Danebury hillfort. Whilst the former approach has been heavily criticised over the last decade, the qualitative methods of the latter have not been evaluated. The first interregional trade in cereals in Britain is currently dated to the Iron Age hillfort societies of the mid 1st millennium bc. Several centuries later, the development of urban settlements in the Late Iron Age and Roman period resulted in populations reliant on food which was produced elsewhere. Using the case study of central-southern Britain, centred on the oppidum (large fortified settlement) and civitas capital of Silchester, this paper presents the first regional quantitative analysis of arable weed seeds in order to identify the origin of the cereals consumed there. Analysis of the weed seeds which were present with the fine sieve by-products of the glume wheat Triticum spelta (spelt) shows that the weed floras of samples from diverse geological areas can be separated on the basis of the soil requirements of individual taxa. A preliminary finding is that, rather than being supplied with cereals from the wider landscape of the chalk region of the Hampshire Downs, the crops were grown close to Late Iron Age Silchester. The method presented here requires further high quality samples to evaluate this conclusion and other instances of cereal movement in the past.